Elementary School Teachers' Perceptions on Video-Based Mathematics Learning in Flipped Classroom Model towards Learning Quality - Zenzen Zakiyah; Karlimah; Syarip Hidayat (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
Teachers' perceptions of video-assisted mathematics instruction in measurement topics within flipped classroom learning models vary. This study explores teachers' perceptions of using video-assisted mathematics instruction in measurement topics in elementary schools. A case study was conducted with 30 elementary school teachers teaching in various regions in Tasikmalaya. Data collection was carried out through questionnaire dissemination and interviews as research instruments. The data analysis technique employed in this study was Interactive Analysis, which involved data reduction, data presentation, and conclusion. The research findings indicate that teachers' perceptions of video-assisted mathematics instruction encompassed cognitive aspects with an average score of 87.50%, affective aspects with an average score of 88.50% and psychomotor aspects with an average score of 89.50%. The results show that most teachers positively perceive using video-assisted mathematics instruction in measurement topics. Teachers state that video-assisted instruction helps students understand measurement concepts and makes learning more engaging and enjoyable for elementary school students.